ANALISIS RANCANGAN TEKNOLOGI PEMISAHAN CO2 PADA LAPANGAN GAS ALAM NATUNA TIMUR DENGAN LAJU GAS DAN KANDUNGAN CO2 SANGAT TINGGI BERDASARKAN PENGARUH TEKANAN UMPAN DAN LAJU GAS UMPAN - Nugrahawan, Siptian
Natural gas resources need to be processed to meet the needs, so that gas sales specifications can be met. CO2 is one type of component that needs to be separated from natural gas. There are several methods of CO2 separation that have been applied that are absorption method, membrane technology, adsorption method, and distillation separation. The choice of CO2 separation method depends on several factors such as the type and concentration of each natural gas forming component, the characteristics, flow rate and volume of feed gas, as well as the final specification of the product to be produced. The CO2 concentration of natural gas varies from a content of less than 20 mole% to more than 80 mole%. There is a problem when the content of CO2 is very high so it is necessary to modify the CO2 level reduction by modifying the equipment or changing the operating conditions to meet the desired CO2 purity. In this study, field conditions and characteristics reviewed is East Natuna Gas Field which has a gas composition of 71% CO2 and 29% methane with modified pressure based on the capability and capacity of available equipment. From the conditions and characteristics of the field, the CO2 method of separation from natural gas using cryogenic distillation was chosen. In this study, the analysis and sensitivity of technical parameters that influence the method of CO2 separation from natural gas using cryogenic distillation. The sensitivity is a change in the parameters of pressure and very high feed gas flow rate into the column. In addition, the calculation of the diameter and height of the distillation column using the calculation of the formula and the results of the simulation using Aspen Hysys V10 software. This study applies a CO2 separation process with cryogenic distillation in Patent Pellegrini 2014 number EP2917666A2 and the desired product specification of CH4 is 99%. The design of the equipment was simulated using two distillation columns with operating pressure at the first distillation column of 45 bar and the temperature of 19.19 oF, and for the second distillation column the operating pressure was reduced to 35 bar. The results are for the 8000 MMSCFD flow rate case obtained the first number of columns as many as 16 with the size of 7.4 meters diameter and 17.66 meters high, while the number of second column of 4 with the size of 8 meters diameter and 22.38 meters high. From these results are still less appropriate with the conditions in the East Natuna Gas Field because offshore limited so need to be studied further for design and other methods in application in the field